Neurocognition: Clinical and Functional Outcomes in Schizophrenia. (January 2014) - Lepage, Martin; Bodnar, Michael; Bowie, Christopher R
Schizophrenia is characterized by significant heterogeneity in outcome. The last decades have witnessed a significant interest in identifying factors that can moderate or influence clinical and functional outcomes in people with schizophrenia. One factor of particular interest is neurocognition, as performance on various measures of cognitive abilities, such as memory, attention, and executive functions, have been consistently related to functional outcome and, to a lesser extent, clinical outcome. This review aims to provide an up-to-date description of recent studies examining the association between neurocognition and clinical and (or) functional outcomes. In the first section, studies examining neurocognitive performance in relation to clinical outcome are examined. When clinical outcome is defined dichotomously (for example, comparing remitted and nonremitted), verbal memory performance consistently exhibits a strong association with clinical status, with the poor outcome group showing the largest deficits. In the second section, studies exploring the relation between neurocognition and various dimensions of functional outcome are reviewed. These dimensions include independent living, social functioning, and vocational functioning, among others. Again, a strong link between neurocognitive deficits and impairments in several aspects of functioning clearly emerges from this review. Finally, several measurement issues are discussed that pertain to the need to standardize definitions of clinical and (or) functional outcomes, the importance of defining cognitive domains consistently across studies, and distinguishing between one's competence to perform tasks and what one actually does in everyday life. Addressing these measurement issues will be key to studies examining the development of effective interventions targeting neurocognitive functions and their impact on clinical and functional outcomes.